2015
DOI: 10.1007/s13197-015-1709-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bamboo shoot powder fortification on physico-chemical, textural and organoleptic characteristics of biscuits

Abstract: Bamboo shoot has attracted significant research and a commercial interest due to its many health-promoting bioactive compounds as well as its effectiveness in decreasing blood pressure, cholesterol and increasing appetite. As availability of fresh shoot is limited due to its seasonality there is need of incorporation of nutrients of shoot to any common food product which is easily available throughout year. Shoots of Bambusa balcooa variety were taken and edible parts were separated. Slices of shoot were boile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
20
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 18 publications
9
20
0
2
Order By: Relevance
“…These results may be occurred because of brown color of DTP and caramelization of sugar substances during biscuit baking. The results are in accordance with [22] [27] whose stated that, as the level of button mushroom powder increased, the L and b values decreased but the a value increased for crumb color of cake indicating that a darker, redder, and less yellow crumb was obtained.…”
Section: Color Parameters Of Biscuitssupporting
confidence: 90%
“…These results may be occurred because of brown color of DTP and caramelization of sugar substances during biscuit baking. The results are in accordance with [22] [27] whose stated that, as the level of button mushroom powder increased, the L and b values decreased but the a value increased for crumb color of cake indicating that a darker, redder, and less yellow crumb was obtained.…”
Section: Color Parameters Of Biscuitssupporting
confidence: 90%
“…This result gives the evidence that all the four forms of dried shoots have high content of phenols and other phytochemicals and could be used as an additive for various food items such as cakes, bread, cookies, ice-cream cones, etc. Boiled shoots of Bambusa balcooa and D. hamiltonii has been used for making products such as candies, biscuits, preserve, chutney, nuggets, cracker and chukh (Sood et al 2013;Choudhury et al 2015;Nimisha et al 2015). Other processed forms of bamboo shoot can also be used to fortify food items.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the addition of KF supports water binding in the batter system. Choudhury et al (2015) reported that an increase in wheat replacement with bamboo shoot powder caused a decrease in gluten content, resulting in an increase in spread ratio in biscuits. Kissell & Yamazaki (1975) revealed that other ingredients, which absorbed water during dough mixing, competed for free water against sugar.…”
Section: Cookie Qualitymentioning
confidence: 99%